Model-based analysis of myocardial strains in left bundle branch block - Taconné, Marion; Owashi, Kimi P.; Galli, Elena; Duchenne, Jürgen; Hubert, Arnaud; Donal, Erwan; Hernàndez, Alfredo I.; Le Rolle, Virginie (Frontiers in Applied Mathematics and Statistics, 2022)
Although observational studies of patients with left bundle branch block (LBBB) have shown a relation between strain morphologies and responses to cardiac resynchronization therapy (CRT), the evaluation of left ventricle (LV) dyssynchrony from echocardiography remains difficult. The objective of this paper is to propose a patient-specific model-based approach to improve the analysis and the interpretation of myocardial strains signals. A system-level model of the cardiovascular system is proposed, integrating: i) the cardiac electrical system, ii) right and left atria, iii) a multi-segment representation of the right and left ventricles and iv) the systemic and pulmonary circulations. After a sensitivity analysis step, model parameters were identified specifically to each patient. The proposed approach was evaluated on data obtained from 10 healthy subjects and 20 LBBB patients with underlying ischaemic (n=10) and non-ischaemic (n=10) cardiomyopathies. A close match is observed between estimated and observed strain signals, with mean RMSE respectively equal to 5.04 +/- 1.02 % and 3.90 +/- 1.40 % in healthy and LBBB cases. The analysis of patient-specific identified parameters, based on bull's-eye representation, shows that strain morphologies are related to both electrical conduction delay, and heterogeneity of contractile levels within the myocardium. The proposed approach represents a step forward the development of personalized LV models for the evaluation of LV dyssynchrony in the field of CRT.